A COMPREHENSIVE REVIEW OF FOREIGN AND DOMESTIC EXPERIENCE IN DESIGNING TECHNOPARKS OF REGIONAL DEVELOPMENT - Hladii, Yehor (Theory and practice of design, 2023)
Today, technology parks play an important role in regional development, contributing to innovation, sustainable economic growth and knowledge sharing. In this scientific article, I present a thorough analysis of the global and domestic experience in designing technology parks with the aim of identifying best practices and key aspects for their successful launch and operation. Purpose. The purpose of this study is to systematize and generalize the most important aspects of technopark design as a tool for stimulating the innovative development of regions. Methodology. To achieve this goal, we used the methods of systematic analysis and literature review, as well as conducted an in-depth analysis of data from various sources. Results. This analysis shows that the successful design of technology parks requires careful strategic planning, development of high-quality infrastructure, effective policy support, cooperation with universities and enterprises, as well as integration into the local socio-cultural context. Scientific novelty. This article highlighted current trends in the design of technology parks, taking into account innovative aspects that help promote innovative development. Practical relevance. Understanding and implementing these key factors will allow regions to effectively use the potential of technology parks to support innovation and sustainable economic growth. These results can be useful for organizers and participants in the process of creating and managing technology parks, as well as for regional authorities and the public, who seek to make their regions centers of technological progress.